A conditional female lethal system for genetic suppression of the global fruit crop pest Drosophila suzukii. Issue 11 (2nd July 2021) - Li, Fang; Yamamoto, Akihiko; Belikoff, Esther J; Berger, Amy; Griffith, Emily H; Scott, Maxwell J
Abstract: BACKGROUND: Drosophila suzukii (Matsumura, 1931, Diptera: Drosophilidae) is a global pest of soft‐skinned fruits such as blueberries, cherries and raspberries. Also known as spotted‐wing drosophila, D. suzukii is native to Asia but is now widely distributed in the Americas and Europe, and presents a serious challenge for growers. Genetic control strategies offer an environmentally friendly approach for the control of D. suzukii . RESULTS: In this study, we developed transgenic strains of D. suzukii that carry dominant conditional female lethal transgenes. When raised in the absence of tetracycline, female D. suzukii die. We show that repeated releases of an excess of transgenic males can suppress D. suzukii populations in laboratory cage trials. CONCLUSION: Our data suggest that the transgenic strain could provide an effective approach for control of this invasive pest of soft‐skinned fruits. Abstract : The FL19 Drosophila suzukii strain carries a dominant female lethal tetracycline‐repressible transgene. Repeated releases of an excess of FL19 males suppresses D. suzukii populations in small cage studies. © 2021 Society of Chemical Industry.